2003
DOI: 10.1080/01926230309736
|View full text |Cite
|
Sign up to set email alerts
|

Role of Connexin32 and beta-Catenin in Tumor Promotion in Mouse Liver

Abstract: Tumor promoters are nonmutagenic chemicals that increase the probability of cancer by accelerating the clonal expansion of cells transformed during tumor initiation. The molecular mechanisms underlying this process are only partly understood but interference with signaling pathways regulating cell division and/or cell death is likely to be important. Ras- and beta-Catenin-dependent signaling is important for both of these processes and ras and beta-catenin genes are known mutational targets in mouse hepatocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Increased murine hepatocarcinogenesis is often linked with MAPK pathway activation resulting from Ha-ras mutation (42,43). In these studies, we did not detect any correlation between Cx32/p27 genotype and the frequency of liver tumors harboring activating Ha-ras codon-61 mutations nor did we detect any β-catenin exon 2 or 3 codon mutations, insertions or deletions.…”
Section: Discussioncontrasting
confidence: 67%
“…Increased murine hepatocarcinogenesis is often linked with MAPK pathway activation resulting from Ha-ras mutation (42,43). In these studies, we did not detect any correlation between Cx32/p27 genotype and the frequency of liver tumors harboring activating Ha-ras codon-61 mutations nor did we detect any β-catenin exon 2 or 3 codon mutations, insertions or deletions.…”
Section: Discussioncontrasting
confidence: 67%
“…Using an immunoprecipitation assay, we first demonstrated that Cx32 interacts with E-cadherin and β-catenin at both tested time point. Although Cx32 co-localization and co-regulation with E-cadherin and β-catenin have been observed in other tissues (Schwarz, Wanke et al 2003) (Kanczuga-Koda, Wincewicz et al 2014) (Ionta, Rosa et al 2012) (Plante, Cyr et al 2005) (Plante, Charbonneau et al 2006), to our knowledge, this is the first report of their physical interaction.…”
Section: Cx32 Interacts With Cx26 and Aj Componentsmentioning
confidence: 67%
“…In human lung cancer, a concurrent reduction in E-cadherin and Cx43 expression is significantly associated with differentiation and progression, and exogenous expression of Cx43 in human pulmonary carcinoma cells significantly induces E-cadherin expression [32]. On the basis of results obtained using Cx32-null mice treated with Nnitrosodimethylamine and phenobarbital, Schwarz et al [33] suggested that the loss of Cx32 function and mutation of b-catenin were important during hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%